Characterization of Antimicrobial Activity of the Symbiotic Bacterium Xenorhabdus Szentirmaii - (:unkn) unknown (My University, 2022)
Xenorhabdus species belonging to the Enterobacteriaceae family are gram negative bacteria that engage in symbiotic associations with the entomopathogenic soil dwelling nematodes of the family Steinernematidae. In this bacterium–nematode mutualistic interaction, both partners benefit from the association. By entering and perforating the insect gut and translocating to the body cavity of hemocoel, the nematodes gain access to the nutrient resource of the insect hemolymph. Xenorhabdus spp are released in the hemolymph in which they produce toxins and immunosuppressive compounds that kill the insect. During the infection Xenorhabdus spp grow to high cell density in the hemolymph. As the nematode invades the insect hemocoel gut microorganisms gain access to the hemocoel. Thus, Xenorhabdus spp compete for space and nutrients with other microorganisms. Xenorhabdus spp produce an array of antimicrobial compounds that act to suppress the growth of the gut microorganisms providing a competitive advantage for growth in the hemolymph. Xenorhabdus spp possess genes that code for non-ribosomal peptide synthetases (NRPS) that use specific amino acids to synthesize peptide antibiotics. Synthesis of the antibiotics requires a prosthetic group that is attached by an enzyme encoded by the ngrA gene. One species, Xenorhabdus szentirmaii was shown to produce high levels of antibiotics. 10 different NRPS gene clusters have been identified in X. szentirmaii that are potentially involved in synthesizing antibiotics. Mutant strains were previously constructed by insertional inactivation in each of the NRPS gene clusters. In the present study, antimicrobial activity of wild type, ngrA and the NRPS mutant strains xsz3 and xsz8 was examined. Antibiotic activity was assessed against Staphylococcus saprophyticus, Aerococcus viridans, and uncharacterized species of yeast, all isolated from the gut of tobacco hornworm (Manduca sexta). Amplification and sequencing of the 5.8S rRNA gene identified the uncharacterized yeast species as Candida orthopsilosis. Three different assays were used to assess the antibiotic activity in strains in which the NRPS genes xsz3 and xsz8 were inactivated. Antibiotic overlay assays showed that antibiotic activity in the xsz3 and xsz8 mutant strains was significantly reduced against S. saprophyticus and C. orthopsilosis whereas against the less sensitive A. viridans the antibiotic activity of the xsz8 strain was more significantly reduced than the xsz3 strain. In cell-free supernatant assays antibiotic activity of the xsz8 strain was more noticeably reduced than the xsz3 strain against S. saprophyticus, whereas against C. orthopsilosis antibiotic activity of the xsz3 strain was more markedly reduced than the xsz8 strain. In ex vivo competition experiments in Grace’s insect medium with S. saprophyticus antibiotic activity of the xsz3 strain was more markedly reduced than in the xsz8 strain. In ex vivo competition experiments in YEPD medium, the ngrA strain that does not produce NRPS antibiotics suppressed the growth C. orthopsilosis as well as the wild type strain indicating that growth inhibition occurred in the absence of NRPS antibiotics. The significance of these findings will be discussed in this study.
Keywords: antibiotics; entomopathogenic nematodes; non-ribosomal peptide synthetases; NRPS mutants; szentirmaii; Xenorhabdus